Clinicopathologic characterization of diseases diagnosed in cockatiels (Nymphicus hollandicus) in the Sertão da Paraíba - Garcia , Dlean da Silva; de Freitas, Gabriel Cavalcante; de Souto, Erick Platiní Ferreira; Wanderley , Vitória Dantas; de Oliveira, Artefio Martins; Dantas, Antonio Flávio Medeiros (Seven Editora, 2024)
The clinical and pathological aspects of diseases diagnosed in cockatiels (Nymphicus hollandicus) in the Sertão da Paraíba, Northeast Brazil, are described. From January 2003 to December 2023, 362 birds were necropsied at the Animal Pathology Laboratory of the Federal University of Campina Grande. Of these, 9 (2.48%) cases were cockatiels, where six were females and three were males, most of the animals were adults and came from the municipality of Patos, Paraíba. The diseases diagnosed were: cloacal prolapse (09/02); dystocia-egg retention (01/09); complete fracture of tibiotarsal bone and fibula (01/09); perforating ulcer and cellomite (01/09); sepsis associated with scabies (09/01); squamous cell carcinoma (01/09); liver cirrhosis (01/09); and osteopathy due to calcium deficiency (01/09). Changes in the cloaca and oviduct were the most frequent conditions, with the others being seen occasionally. Although they involve different causes, most of the diseases observed are directly or indirectly related to sanitary and nutritional management practices. Highlighting the importance of knowledge about the possible diseases that can affect this species, whether it is raised freely or domiciled. DOI:https://doi.org/10.56238/sevened2024.023-020